The strategy of simulation effects of wind speed, variation of turbine blades and it’s interaction to power generated by vertical axis wind turbine using NACA 2412 - Purwono, Bambang Sugiyono Agus; ., Masroni; Setiawan, Awan; Subali Patma, Tundung; Bagus Suardika, Ida (International Journal of Engineering and Technology, 2017)
The objective of this paper is to simulate the effects upon the wind speed, variation of turbine blades and interaction of wind speed and variation of turbine blades to the power capacity generated by Vertical Axis Wind Turbine (VAWT) using NACA 2412 and to stratify the power capacity generated by the VAWT simulation. The research backgrounds are the wind-energy potential in Indonesia is about 9.290 MW and has already elaborated by Ministry of Mining, and Energy Resources is about 50 MW. This wind energy is environmentally (clean energy), economically (cheapest), easy to operate and easy to maintain, also renewable energy. The method of analysis is quantitative approach using two way classification (analysis of variance or design of experiments). The research variables are wind speed, variation of turbine blades and this interaction among independent variables and the power capacity as dependent variables. Data wind speed simulation vary from 3 m/s till 6 m/s. The quantity of turbine blades vary from 3 till 8 units. The finding from this research is accepted the null hypothesis or not differ significantly at 5% from each independent variable. The scenario and the parameters during the strategy development use turbine blades, wind speed and power generated by VAWT and the maximum power generated is 16.38 watt. The wind speed is 6 m/s and the number of turbine blade is 4 units. However, the minimum power generated by VAWT is 0.45 watt, the wind speed is 6 m/s and the number of turbine blade is 3 units.
Keywords: VAWT; NACA 2412; Wind Speed; Turbine Blades; Power; Renewable Energy.